Dry etching of Co2MnSi magnetic thin films using a CH3OH/Ar based inductively coupled plasma. (January 2015) - Garay, Adrian Adalberto; Hwang, Su Min; Chung, Chee Won
Abstract: The inductively coupled plasma etching characteristics of Co2 MnSi thin films patterned using a TiN hard mask were investigated by the addition of CH3 OH to Ar gas. As the CH3 OH concentration increased, the etch rates of Co2 MnSi magnetic thin films and TiN hard mask decreased, but the etch profile improved. The effects of rf power, dc-bias voltage and gas pressure on the etch rate and etch profile were also investigated. The etch rate and etch profile degree of anisotropy increased with increasing rf power and dc-bias voltage and decreasing gas pressure. Optical emission spectroscopy analysis revealed that [H], [O], [CO], [OH], [CH3 O] and [Ar] species in the CH3 OH/Ar plasma played a key role in achieving a good etch profile. Highlights: ICPRIE of Co2 MnSi films was investigated using a CH3 OH/Ar. As CH3 OH concentration increased etch rate and etch profile anisotropy increased. By increasing rf power and dc-bias etch rate and etch profile anisotropy increased. Decreasing pressure increased etch rate and degree of anisotropy. OES analysis was done to understand etch mechanism.